2017
DOI: 10.1002/jor.23779
|View full text |Cite
|
Sign up to set email alerts
|

Osteophytes and fracture calluses share developmental milestones and are diminished by unloading

Abstract: Osteophytes are a typical radiographic finding during osteoarthritis (OA), but the mechanisms leading to their formation are not well known. Comparatively, fracture calluses have been studied extensively; therefore, drawing comparisons between osteophytes and fracture calluses may lead to a deeper understanding of osteophyte formation. In this study, we compared the time courses of osteophyte and fracture callus formation, and investigated mechanisms contributing to development of these structure. Additionally… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
21
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 49 publications
1
21
0
Order By: Relevance
“…(ii) Dayal et al reported a reduced laxity in anterior posterior with osteophyte growth 19 . (iii) In a mouse model following anterior cruciate ligament transection, the initial increase in joint laxity was reduced significantly over time and this development correlated with the formation of osteophytes 20 . Yet, a clinical study to confirm improvement of OA-related pain and immobilization during early disease stages is still lacking.…”
mentioning
confidence: 95%
“…(ii) Dayal et al reported a reduced laxity in anterior posterior with osteophyte growth 19 . (iii) In a mouse model following anterior cruciate ligament transection, the initial increase in joint laxity was reduced significantly over time and this development correlated with the formation of osteophytes 20 . Yet, a clinical study to confirm improvement of OA-related pain and immobilization during early disease stages is still lacking.…”
mentioning
confidence: 95%
“…The sections were stained with Safranin‐O–fast‐green to assess osteophyte formation and articular cartilage degeneration. The osteophyte (including chondrophyte) areas were quantified using freehand traces in ImageJ (National Institutes of Health, Bethesda, MD) . Histologic grading of articular cartilage damage severity was performed using the scoring system reported by Kamekura et al, which consisted of a 0‐4 scale for cartilage degeneration (0: No apparent changes; 1: Loss of superficial zone in articular cartilage; 2: Defects limited above tidemark; 3: Defects extending to calcified cartilage; 4: Exposure of subchondral bone) and a 0‐3 scale for osteophyte formation (0: None; 1: Formation of cartilage‐like tissues; 2: Increase in cartilaginous matrix; 3: Endochondral ossification).…”
Section: Methodsmentioning
confidence: 99%
“…ImageJ (National Institutes of Health, Bethesda, MD). 21,22 Histologic grading of articular cartilage damage severity was performed using the scoring system reported by Kamekura et al, 7 which consisted of a 0-4 scale for cartilage degeneration (0: No apparent changes; 1: Loss of superficial zone in articular cartilage; 2: Defects limited above tidemark; 3: Defects extending to calcified cartilage; 4: Exposure of subchondral bone) and a 0-3 scale for osteophyte formation (0: None; 1: Formation of cartilage-like tissues; 2: Increase in cartilaginous matrix; 3: Endochondral ossification). Previously, there were multiple scoring systems for assessing a murine osteoarthritis model.…”
mentioning
confidence: 99%
“…Secondly, pain, as the rst symptom and main treatment factor of KOA patients, seriously affects the physical and mental health of patients [10]. It has been found that KOA pain originates not only from peripheral nerve responses caused by joint and surrounding tissue injury or in ammatory stimulation of peripheral receptors [11,12], but also from pain sensitization of central neurons caused by increased activity of descending ber pain pathways or loss of anti-in ammatory effects in the central nervous system [13,14]. There has also been evidence in recent years that [15,16], the source of KOA pain is not limited to peripheral and central nervous system sensitization, but also affected by a range of sociocultural and psychological factors, including underlying anxiety and depression [17].…”
Section: Background and Rationale {6a6b}mentioning
confidence: 99%